MENGENAL PENYAKIT BATU EMPEDU - Uswatun Hasanah (Universitas Negeri Medan, 2015)
ABSTRACT Gallstones are crystalline rock pile contained in the gall bladder. Actually, not only in the gallbladder, but also found in the bile ducts and can also be found in the liver. Stone found in the gallbladder is called cholelithiasis, while stones in the bile ducts called koledokolitiasis. Gallstone formation last long, 10-15 years. Gallstones are mute or silent stone, often without any complaints and symptoms manifest. Depending upon the size and number of gallstones are formed as well as the location, severity of symptoms can vary. Elements forming gallstones are cholesterol and calcium. More than 90% of gallstones are cholesterol stones (cholesterol composition > 50%) or mixed form (20-50% cholesterol element) and the remaining 10% is pigment stones (calcium dominant element and cholesterol <20%). Gallstone risk factors known by the acronym 4F, the Forty, Female, Fat, Family. That is, gallstones are more common in those aged over 40 years old, female, overweight and have a family history of gallstones. Medications can be used to break up gallstones. Treatment requires at least 6 to 12 months and managed to dissolve stones in 40-80% of cases. The use of drugs is recommended when mild symptoms and small stones or surgery is considered too risky. The risk of gallstone formation can be reduced by living a healthy lifestyle, especially to keep the weight off. Applying a diet that does not contain a lot of saturated fat helps reduce the risk of gallstones. Kata Kunci : Batu empedu, kolesterol, pigmen, gaya hidup sehat